The Legal Position of Customary Land in National Land Law After the Enactment of ATR/BPN Ministerial Regulation Number 18 of 2019 - D. Krismantoro (PT Publikasiku Academic Solution, 2023)
The purpose of this study is to determine the status and position of customary land in national law after the enactment of the Regulation of the Minister of ATR / BPN Number 18 of 2019 concerning procedures for administering customary land unitary customary law communities. This is done so that there is legal certainty regarding regulations on customary land rights, so as not to become controversial. The research method used in this study is the normative juridical research method. The type of approach chosen to answer the problem formulation is the statute approach (the approach of using laws and regulations and draft laws and regulations), namely with various rules or legal products related to matters governing land in Indonesia relating to indigenous peoples. The results of this study are that: The legal position of customary land after the enactment of Regulation of ATR No. 18 of 2019, juridically does not affect the existence of communal rights over land, as long as it does not conflict with the regulations of the Unitary State of the Republic of Indonesia and its regulatory procedures.